2001
DOI: 10.1128/cdli.8.3.624-627.2001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Antibody againstErysipelothrix rhusiopathiaein Cattle

Abstract: Serum samples collected from 854 cattle in nine prefectures of Japan, from Hokkaido to Okinawa, between 1988 and 1992 were examined for presence of antibodies against Erysipelothrix rhusiopathiae by growth agglutination test. Most of the sera showed positive reactions, and the antibody titers ranged from below 4 to above 128. Seventy-six percent of the sera showed titers of 32 or above, and 34% showed titers of 128 or above. The titers had a tendency to be higher in the south and lower in the north and were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 10 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…This data could indicate that Erysipelothrix is mainly transmitted by pigs although cattle may also act as a vehicle for its distribution [5,16]. In support of this, Erysipelothrix was isolated from cattle slurry [3] which could enhance the bacterium's ability to spread as Erysipelothrix can survive in soil contaminated with faecal material [4]. Current methods of antibody detection in cattle have been carried out using solely GAT.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…This data could indicate that Erysipelothrix is mainly transmitted by pigs although cattle may also act as a vehicle for its distribution [5,16]. In support of this, Erysipelothrix was isolated from cattle slurry [3] which could enhance the bacterium's ability to spread as Erysipelothrix can survive in soil contaminated with faecal material [4]. Current methods of antibody detection in cattle have been carried out using solely GAT.…”
Section: Introductionmentioning
confidence: 82%
“…An epidemiological follow-up study using the growth agglutination test (GAT) to detect antibodies anti-Erysipelothrix in Japanese cattle found that 76% of 854 healthy cattle had detectable antibodies [3]. The same study also found a higher rate of seropositive cattle in areas with concurrent swine industry [3]. This data could indicate that Erysipelothrix is mainly transmitted by pigs although cattle may also act as a vehicle for its distribution [5,16].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations